Los Trabajadores Portuarios Chilenos y la Experiencia de la Eventualidad: Los Conflictos por la Redondilla en Los Muelles Salitreros (1916-1923) - Santibáñez-Rebolledo, C (Pontificia Universidad Catolica de Chile, 2017)
This article studies the conflictive implementation and repeal of a work shift distribution system known as "redondilla" in the saltpeter mine operation sites. In the context of temporary employment, which followed the dismantling of nineteenth century port workers trade unions, this state and shipping company imposed shift system implemented at northern Chilean ports, rooted itself in the name of labor demands it was intended to contain; a persistent propensity of day laborers and dockworkers directly taking control of the sale of their labor force, effectively removing from the middle those men that administered the hiring. The result of this tension in the end culminated in the first effort of governmental "de-casualization" on the Chilean coasts between 1922 and 1923. © Historia (Santiago) 2017.